(3 x 10^19) + (2 x 10^19) + (2 x 10^19)

Question

(3 x 10^19) + (2 x 10^19) + (2 x 10^19)

in progress 0
Ariana 2 weeks 2021-09-08T23:56:23+00:00 2 Answers 0

Answers ( )

    0
    2021-09-08T23:57:52+00:00

    Answer:

    7 * 10^19.

    Step-by-step explanation:

    (3 x 10^19) + (2 x 10^19) + (2 x 10^19)

    = (3 + 2 + 2) *  10^19

    = 7 * 10^19

    0
    2021-09-08T23:57:56+00:00

    Step-by-step explanation:

    (3  \times 10^{19}) + (2  \times  10^{19}) + (2  \times  10^{19}) \\  \\ 3  \times 10^{19} + 2  \times 10^{19} + 2 \times 10^{19} \\  \\  = (3 + 2 + 2)\times 10^{19}  \\  \\  = 7 \times  10^{19}

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )